2017
DOI: 10.1002/hec.3540
|View full text |Cite
|
Sign up to set email alerts
|

How do hospital‐specialty characteristics influence health system responsiveness? An empirical evaluation of in‐patient care in the Italian region of Emilia‐Romagna

Abstract: Several studies of health system responsiveness focus on the demand-side by investigating the association between socio-demographic characteristics of patients and their reported level of responsiveness. However, little is known about the influence of supply-side factors. This paper addresses that research gap by analysing the role of hospital-specialty characteristics in explaining variations in patients' evaluation of responsiveness from a sample of about 38,700 in-patients treated in public hospitals within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Additionally, our findings of lower levels of positive opinions about the emergency care department post-reform may reinforce those of Fiorentini et al (2017), who recorded a strong association between subjective and objective measures of health care satisfaction. Therefore, we corroborate previous findings that patients' self-reported measures can be considered valid predictors of more objective measures of responsiveness and could be used as tools to evaluate the performance of health systems.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Additionally, our findings of lower levels of positive opinions about the emergency care department post-reform may reinforce those of Fiorentini et al (2017), who recorded a strong association between subjective and objective measures of health care satisfaction. Therefore, we corroborate previous findings that patients' self-reported measures can be considered valid predictors of more objective measures of responsiveness and could be used as tools to evaluate the performance of health systems.…”
Section: Discussionsupporting
confidence: 85%
“…While the primary focus of the reform is health care utilization, a parameter that can be directly determined, the impact of the law on user perceptions about the health system, or on health status, is less straightforward. Taking a recent study (Fiorentini et al, 2017) reporting a strong correlation between objective and subjective opinions about health system responsiveness, we offer the conjecture that the 2012 reform may have had a negative effect on the perceived quality of care on the part of undocumented persons. However, it is also plausible that, in times of restricted access to health care, individual expectations may be lower (Gallo and Gené-Badía, 2013) and thus positive opinions about the health system may even increase as a result.…”
Section: Datamentioning
confidence: 99%
“…Such surveys have not been repeated since, so there is no way of knowing whether countries have improved/ regressed in relation to their national responsiveness assessment. More recent studies have applied the tool to measure responsiveness at the meso-level (organization/ facility) or for specific services or programs [70][71][72]. There are also responsiveness assessments for the health system building blocks.…”
Section: Description Of Categorization 1: 'Unidirectional User-service Interface'mentioning
confidence: 99%
“…In the report, the WHO developed a framework for assessing the overall performance of a health system taking into account the following items: level and distribution of health, level and distribution of responsiveness, and fairness in financial contribution. Of these items, those related to responsiveness have received increasing attention in the literature [2][3][4][5]. Health system responsiveness concerns the way individuals are treated and the environment in which they are treated by the health system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the experiences that people report with regard to non-clinical factors have typically been used to quantify the level of health system responsiveness in these domains. Some authors have shown that subjective measures may be a good proxy of the real responsiveness of health systems [2].…”
Section: Introductionmentioning
confidence: 99%